Study of Optical, Structural, Thermal and Dielectric Properties of Poly(vinylidene diflouride)/Cuprous Oxide Polymer Nanocomposites - Behera, M.; Biswal, S.K.; Panda, Bhabani S.; Ahemad, Mohammed A. (Asian Journal of Chemistry, 2019)
Herein, a development of cuprous oxide (Cu2O)/polyvinylidene difluoride (PVDF) polymer nanocomposite (PNC) films by solution casting route is reported. The nanocomposite films were characterized using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA) and LCR meter. Formation of a broad band near 465 nm for polymer nanocomposite suggests that Cu2O nanoparticles are present in the film. Some of the vibrational bands of PVDF were slightly shifted from their original position and the intensity of some bands were found to increase in presence of nanoparticles. Such features reveal that some interaction occurs between PVDF and Cu2O nanoparticles. Scanning electron microscope (SEM) images show that the nanoparticles are interconnected to each other through PVDF polymer chain. Crystalline nature of Cu2O nanoparticles in the film was confirmed from XRD pattern. Thermogravimetric analysis shows that thermal stability of neat PVDF has increased in presence of nanoparticles. The neat PVDF showed dielectric constant value of 8 at frequency 100 Hz, while that of 1 wt% Cu2O doped PVDF polymer nanocomposite has exhibited dielectric constant value 175 at the same frequency.